Biodegradable polyester resin-made foamed sheet and biodegradable polyester resin-made foamed molded body

The biodegradable polyester resin foam sheet, formulated with a specific ratio of aliphatic and aromatic copolyester resins, addresses the issue of impact resistance in biodegradable foams, offering enhanced performance and sustainability.

JP2025052706APending Publication Date: 2025-04-07SEKISUI PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023161556
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Biodegradable polyester resin foam sheets and molded articles lack sufficient impact resistance, making them unsuitable for applications requiring robustness.

Method used

A biodegradable polyester resin foam sheet is developed by foaming a resin composition containing a biodegradable aliphatic polyester resin and a biodegradable aliphatic-aromatic copolyester resin, with a mass ratio of 75:25 to 97:3, and optimized properties such as maximum point energy, flexibility, and surface hardness.

Benefits of technology

The resulting biodegradable polyester resin foam sheet exhibits excellent impact resistance, flexibility, and processability, making it suitable for various applications while maintaining biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052706000001_ABST
    Figure 2025052706000001_ABST
Patent Text Reader

Abstract

To provide a biodegradable polyester resin-made foamed sheet capable of developing excellent impact resistance, and a biodegradable polyester resin-made foamed molded body obtained by molding such a biodegradable polyester resin-made foamed sheet.SOLUTION: A biodegradable polyester resin-made foamed sheet according to an embodiment of the present invention is a biodegradable polyester resin-made foamed sheet obtained by foaming a resin composition (C) which includes biodegradable aliphatic polyester resin (A) and biodegradable aliphatic-aromatic copolyester resin (B), in the biodegradable polyester resin-made foamed sheet, a mass ratio of the biodegradable aliphatic polyester resin (A) to the biodegradable aliphatic-aromatic copolyester resin (B) is (A):(B)=75:25 to 97:3.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a biodegradable polyester resin foam sheet and a biodegradable polyester resin foam molded article. [Background technology]

[0002] Resin foam sheets and resin foam molded articles are lightweight, have excellent cushioning properties, and can be easily molded into a variety of shapes, so they are used as raw materials for various molded products, including packaging materials.

[0003] In recent years, resin foam sheets and resin foam molded articles have been used in large quantities and then discarded in large quantities. This places a heavy burden on the environment and is a factor in various social problems, such as global warming, resource depletion, and waste disposal. Therefore, foam sheets and foam molded articles made from biodegradable polyester resins, such as polylactic acid resins, have been proposed, which are biodegradable, have a small environmental impact, and can be produced relatively inexpensively.

[0004] However, foam sheets and foam-molded articles made from biodegradable polyester resins such as polylactic acid resins have problems in that they are hard and brittle and have poor impact resistance, and therefore, various industrial fields have been demanding foam sheets and foam-molded articles made from biodegradable polyester resins that have sufficient impact resistance.

[0005] A technique for improving the impact resistance of non-foamed biodegradable polyester resin molded articles has been reported (Patent Document 1). However, because the properties of non-foamed resins and foamed resins are completely different, even if such a technique is applied to foamed sheets or foamed molded articles using biodegradable polyester resins, sufficient impact resistance cannot be achieved.

[0006] On the other hand, as a technology for improving the impact resistance of polylactic acid-based resin foam sheets, a polylactic acid-based resin foam sheet obtained from a polylactic acid-based resin composition containing a polylactic acid-based resin and 8 to 28 parts by mass of a core-shell butadiene-based elastomer as an impact resistance improver per 100 parts by mass of the polylactic acid-based resin has been reported (Patent Document 2). However, there is still room for improvement in impact resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Laid-Open No. 2004-269588 [Patent Document 2] Japanese Patent Publication No. 2022-57271 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a biodegradable polyester resin foam sheet that can exhibit excellent impact resistance, and to provide a biodegradable polyester resin foam molded article obtained by molding such a biodegradable polyester resin foam sheet. [Means for solving the problem]

[0009] [1] A biodegradable polyester resin foam sheet according to an embodiment of the present invention is a biodegradable polyester resin foam sheet obtained by foaming a resin composition (C) containing a biodegradable aliphatic polyester resin (A) and a biodegradable aliphatic-aromatic copolyester resin (B), wherein the mass ratio of the biodegradable aliphatic polyester resin (A) to the biodegradable aliphatic-aromatic copolyester resin (B) is (A):(B)=75:25 to 97:3. [2] The biodegradable polyester resin foam sheet according to [1] above may have a peak energy of 0.30 J or more as measured in accordance with ASTM D-3763-15. [3] The biodegradable polyester resin foam sheet according to [1] or [2] above may have a flexibility of 2.0 N / mm to 9.0 N / mm as measured in accordance with JIS K7171:2016. [4] The biodegradable polyester resin foam sheet according to any one of [1] to [3] above may have a surface hardness of 94 or less. [5] The biodegradable polyester resin foam sheet according to any one of the above [1] to [4] may have a thickness of 0.5 mm to 7 mm. [6] The biodegradable polyester resin foam sheet according to any one of [1] to [5] above may have an open cell ratio of 50% or less. [7] The biodegradable polyester resin foam sheet according to any one of the above items [1] to [6] may have an expansion ratio of 4 to 20 times. [8] In the biodegradable polyester resin foam sheet according to any one of [1] to [7] above, the biodegradable aliphatic polyester resin (A) may have a melt tension at 190°C of 20 cN or more. [9] In the biodegradable polyester resin foam sheet according to any one of [1] to [8] above, the biodegradable aliphatic polyester resin (A) may have an MFR of 5.0 g / 10 min or less.

[10] In the biodegradable polyester resin foam sheet according to any one of the above items [1] to [9], the biodegradable aliphatic polyester resin (A) may be a polylactic acid resin (P).

[11] In the biodegradable polyester resin foam sheet according to the above item

[10] , the polylactic acid resin (P) may be a modified polylactic acid resin.

[12] In the biodegradable polyester resin foam sheet according to any one of [1] to

[11] above, the biodegradable aliphatic-aromatic copolyester resin (B) may be polybutylene adipate terephthalate.

[13] A biodegradable polyester resin foam molded article obtained by molding the biodegradable polyester resin foam sheet according to any one of [1] to

[12] above. [Effects of the Invention]

[0010] According to an embodiment of the present invention, it is possible to provide a biodegradable polyester resin foam sheet that can exhibit excellent impact resistance, and also to provide a biodegradable polyester resin foam molded article obtained by molding such a biodegradable polyester resin foam sheet. [Brief explanation of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing one preferred configuration of an extruder used in producing a modified polylactic acid resin. [Figure 2] FIG. 1 is a schematic diagram showing a preferred configuration of a production apparatus suitable for producing a biodegradable polyester resin foam sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0012] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0013] In this specification, "polylactic acid resin (P)" means "modified polylactic acid resin" or "unmodified polylactic acid resin." In this specification, when "polylactic acid resin" is simply stated without the term "polylactic acid resin (P)," it means unmodified polylactic acid resin. Here, "unmodified polylactic acid resin" refers to polylactic acid resin that has not been modified, typically a commonly available polylactic acid resin, and not a modified polylactic acid resin that has been modified.

[0014] In this specification, the term "substantially 100% by mass" means that the presence of a trace amount of unintentionally mixed impurities (for example, less than 1% by mass) can be ignored.

[0015] <<1. Biodegradable polyester resin foam sheet>> The biodegradable polyester resin foam sheet according to an embodiment of the present invention is obtained by foaming a resin composition (C). In one preferred embodiment, the biodegradable polyester resin foam sheet according to an embodiment of the present invention is obtained by melt-kneading and extrusion-foaming the resin composition (C) in an extruder.

[0016] The biodegradable polyester resin foam sheet according to an embodiment of the present invention preferably has a maximum point energy of 0.30 J or more, more preferably 0.33 J or more, even more preferably 0.35 J or more, even more preferably 0.37 J or more, particularly preferably 0.39 J or more, and most preferably 0.40 J or more, as measured in accordance with ASTM D-3763-15. The upper limit of the maximum point energy is preferably 5.0 J or less, although a higher upper limit is preferable to prevent excessive softness or a decrease in container strength. When the maximum point energy is within the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention can exhibit excellent impact resistance. When the maximum point energy is too low outside the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention may become hard and brittle, resulting in poor impact resistance.

[0017] The flexibility of the biodegradable polyester resin foam sheet according to an embodiment of the present invention, as measured in accordance with JIS K7171:2016, is preferably 2.0 N / mm to 9.0 N / mm, more preferably 2.0 N / mm to 8.5 N / mm, even more preferably 2.0 N / mm to 8.0 N / mm, particularly preferably 2.2 N / mm to 8.0 N / mm, and most preferably 2.5 N / mm to 8.0 N / mm. When the flexibility is within the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention is neither too hard nor too soft and can exhibit excellent moldability and processability. If the flexibility is too high outside the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention may be too hard and may have poor processability. If the flexibility is too low outside the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention may be too soft and may result in poor strength of molded products.

[0018] The biodegradable polyester resin foam sheet according to an embodiment of the present invention has a surface hardness of preferably 94 or less, more preferably 93 or less, even more preferably 92 or less, particularly preferably 91 or less, and most preferably 90 or less. The lower limit of the surface hardness is preferably 50 or more, since this may result in a decrease in processability, such as excessive softness or increased susceptibility to burrs. As long as the surface hardness is within the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention can exhibit excellent processability. If the surface hardness is too high, outside the above range, problems such as burrs may occur during molding.

[0019] The thickness of the biodegradable polyester resin foam sheet according to an embodiment of the present invention can be appropriately set depending on the purpose. The thickness of the biodegradable polyester resin foam sheet according to an embodiment of the present invention is preferably 0.5 mm to 7 mm, more preferably 0.5 mm to 5 mm, even more preferably 0.7 mm to 5 mm, and particularly preferably 0.7 mm to 3 mm. When the thickness is within the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention can have excellent shape retention and thermoformability. If the thickness is outside the above range and is too small, the shape retention of the biodegradable polyester resin foam sheet according to an embodiment of the present invention may be reduced. If the thickness is outside the above range and is too large, the thermoformability of the biodegradable polyester resin foam sheet according to an embodiment of the present invention may be reduced.

[0020] The biodegradable polyester resin foam sheet according to an embodiment of the present invention has an open cell ratio of preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, even more preferably 20% or less, and particularly preferably 15% or less. The lower limit of the open cell ratio is preferably as low as possible, and is preferably 0% or more. When the open cell ratio of the biodegradable polyester resin foam sheet according to an embodiment of the present invention is within the above range, the biodegradable polyester resin foam sheet according to an embodiment of the present invention can exhibit better impact resistance. When the open cell ratio is too high outside the above range, the impact resistance of the biodegradable polyester resin foam sheet according to an embodiment of the present invention may be reduced due to cell collapse.

[0021] The biodegradable polyester resin foam sheet according to the embodiment of the present invention preferably has an apparent density of 0.063 g / cm in order to further exhibit the effects of the present invention. 3 ~0.33g / cm 3 and more preferably 0.068 g / cm 3 ~0.31g / cm 3 and more preferably 0.072 g / cm 3 ~0.31g / cm 3 and particularly preferably 0.078 g / cm3 ~0.31g / cm 3 is.

[0022] The biodegradable polyester resin foam sheet according to an embodiment of the present invention has an expansion ratio of preferably 4 to 20 times, more preferably 4 to 15 times, even more preferably 4 to 12 times, and particularly preferably 4 to 10 times, in order to further exhibit the effects of the present invention.

[0023] ≪1-1. Resin composition (C)≫ A representative embodiment of the biodegradable polyester resin foam sheet according to the present invention is obtained by melt-kneading the resin composition (C) in an extruder and extrusion-foaming it.

[0024] The resin composition (C) contains a biodegradable aliphatic polyester resin (A) and a biodegradable aliphatic-aromatic copolyester resin (B).

[0025] The total content of the biodegradable aliphatic polyester resin (A) and the biodegradable aliphatic-aromatic copolyester resin (B) in the resin composition (C) is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 85% by mass to 100% by mass, in order to achieve the effects of the present invention.

[0026] In the resin composition (C), the mass ratio (A):(B) of the biodegradable aliphatic polyester resin (A) to the biodegradable aliphatic-aromatic copolyester resin (B) is preferably 75:25 to 97:3, more preferably 75:25 to 95:5, even more preferably 75:25 to 93:7, particularly preferably 75:25 to 91:9, and most preferably 75:25 to 90:10, in order to achieve the effects of the present invention.

[0027] <1-1-a. Biodegradable Aliphatic Polyester Resin (A)> As the biodegradable aliphatic polyester resin (A), any appropriate biodegradable aliphatic polyester resin can be used as long as it does not impair the effects of the present invention. The biodegradable aliphatic polyester resin (A) may be one type or two or more types.

[0028] In order to further exert the effects of the present invention, the biodegradable aliphatic polyester resin (A) preferably has a melt tension at 190°C of 20 cN or more, more preferably 20 cN to 100 cN, even more preferably 30 cN to 80 cN, particularly preferably 40 cN to 70 cN, and most preferably more than 40 cN to 60 cN or less.

[0029] In order to further exert the effects of the present invention, the biodegradable aliphatic polyester resin (A) has an MFR of 5.0 g / 10 min or less, more preferably 0.2 g / 10 min to 5.0 g / 10 min, even more preferably 0.5 g / 10 min to 4.5 g / 10 min, particularly preferably 1.0 g / 10 min to 4.0 g / 10 min, and most preferably 1.0 g / 10 min to 3.5 g / 10 min. When the MFR of the biodegradable aliphatic polyester resin (A) is within the above range, it can exhibit appropriate fluidity when hot-melted, and the effects of the present invention can be further exerted.

[0030] The biodegradable aliphatic polyester resin (A) is preferably a polylactic acid resin (P) in that it can further exert the effects of the present invention.

[0031] The polylactic acid resin (P) may be a modified polylactic acid resin, an unmodified polylactic acid resin, or a mixture thereof.

[0032] The polylactic acid resin (P) typically contains a modified polylactic acid resin as a main component, and the content of the modified polylactic acid resin in the polylactic acid resin (P) is preferably more than 50% by mass, more preferably 70% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably substantially 100% by mass.

[0033] The modified polylactic acid resin is preferably obtained by melt-kneading a polylactic acid resin composition containing a polylactic acid resin and a modifier in an extruder.

[0034] The polylactic acid resin may be a homopolymer of lactic acid or a copolymer of lactic acid with other monomers, such as aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides.

[0035] The lactic acid constituting the polylactic acid resin may be either the L- or D-form, or both the L- and D-forms. That is, the polylactic acid resin, which is a homopolymer of lactic acid, may be any of poly(L-lactic acid) resin, poly(D-lactic acid) resin, and poly(DL-lactic acid) resin.

[0036] Examples of hydroxycarboxylic acids other than lactic acid include glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, and 6-hydroxycaproic acid.

[0037] Examples of aliphatic polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentyl glycol, tetramethylene glycol, and 1,4-cyclohexanedimethanol.

[0038] Examples of the aliphatic polycarboxylic acid include oxalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, undecanedioic acid, and dodecanedioic acid. The aliphatic polycarboxylic acid may also be an acid anhydride.

[0039] Examples of polyfunctional polysaccharides include cellulose, cellulose nitrate, methyl cellulose, ethyl cellulose, celluloid, viscose rayon, regenerated cellulose, cellophane, cupra, cuprammonium rayon, cuprophane, Bemberg, hemicellulol, starch, acropectin, dextrin, dextran, glycogen, pectin, chitin, chitosan, gum arabic, guar gum, locust bean gum, and acacia gum.

[0040] In the polylactic acid resin, the content of structural portions derived from lactic acid (L- and D-forms) in the molecule is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and most preferably 90% by mass or more.

[0041] At least a part of the polylactic acid resin used as a raw material may be recycled.

[0042] The modifier exerts the effect of increasing the molecular weight of the polylactic acid resin and imparting a crosslinked structure or a long-chain branched structure to the molecular structure of the polylactic acid resin.

[0043] The modifier may be of only one type, or of two or more types.

[0044] To increase the molecular weight of polylactic acid resin, a chain extender such as carbodiimide can be used as a modifier. Modification using a chain extender can be achieved by using a compound having one or more functional groups capable of undergoing a condensation reaction with hydroxyl or carboxyl groups present in the molecular structure of polylactic acid resin, such as an acrylic organic compound, an epoxy organic compound, or an isocyanate organic compound. That is, the molecular weight of polylactic acid resin can be increased by using a chain extender such as carbodiimide to bond an acrylic organic compound, an epoxy organic compound, an isocyanate organic compound, or the like to the polylactic acid resin.

[0045] To impart a crosslinked structure or a long-chain branched structure to the molecular structure of polylactic acid resin, for example, a radical initiator can be used as a modifier. In this case, polylactic acid resins are reacted with each other using the radical initiator. When polylactic acid resins are reacted with each other using a radical initiator with appropriate reactivity, for example, the decomposition starting points of the polylactic acid resin in the extruder are attacked by free radicals generated by the radical initiator, and these points become crosslinked points (branching points) and can be stabilized. By undergoing such modification, the thermal stability of the polylactic acid resin is increased and it becomes less susceptible to molecular weight degradation when passing through the extruder.

[0046] Examples of the radical initiator include organic peroxides, azo compounds, and halogen molecules, with organic peroxides being preferred.

[0047] Examples of organic peroxides include peroxyesters, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxydicarbonates, peroxyketals, and ketone peroxides.

[0048] Examples of peroxyesters include t-butylperoxy 2-ethylhexyl carbonate, t-hexylperoxy isopropyl monocarbonate, t-hexylperoxybenzoate, t-butylperoxybenzoate, t-butylperoxy laurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxy acetate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and t-butylperoxy isopropyl monocarbonate.

[0049] Examples of hydroperoxides include permethane hydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide.

[0050] Examples of dialkyl peroxides include dicumyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-di(t-butylperoxy)-hexyne-3.

[0051] Examples of diacyl peroxides include dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, and di(3-methylbenzoyl) peroxide.

[0052] Examples of peroxydicarbonates include di(2-ethylhexyl) peroxydicarbonate and diisopropyl peroxydicarbonate.

[0053] Examples of peroxyketals include 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, 1,1-di-t-butylperoxycyclohexane, 2,2-di(t-butylperoxy)-butane, n-butyl 4,4-di-(t-butylperoxy)valerate, and 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane.

[0054] Examples of ketone peroxides include methyl ethyl ketone peroxide and acetylacetone peroxide.

[0055] Modification with organic peroxides may result in the modified polylactic acid resin being contaminated with components having excessively large molecular weights that gel when thermally melted, or may cause odor problems due to decomposition residues of the organic peroxide. Peroxyesters are preferred as the organic peroxides, as they can prevent such problems and easily modify the polylactic acid resin to a state suitable for foaming. Among peroxyesters, peroxycarbonate-based organic peroxides such as peroxymonocarbonate and peroxydicarbonate are preferred. Among peroxycarbonate-based organic peroxides, peroxymonocarbonate-based organic peroxides are preferred, with t-butylperoxyisopropyl monocarbonate being more preferred.

[0056] The amount of organic peroxide used depends on the molecular weight, etc., but in order to further exhibit the effects of the present invention, it is preferably 0.1 part by mass or more, more preferably 0.2 part by mass or more, and even more preferably 0.3 part by mass or more, relative to 100 parts by mass of polylactic acid resin. The upper limit of the amount of organic peroxide used is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1.0 part by mass or less.

[0057] A polylactic acid resin composition containing a polylactic acid resin and a modifier may contain any appropriate component other than the polylactic acid resin and the modifier, as long as the effects of the present invention are not impaired. The total content of the polylactic acid resin and the modifier in the polylactic acid resin composition containing a polylactic acid resin and a modifier is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and particularly preferably 95% by mass to 100% by mass.

[0058] The polylactic acid resin composition containing the polylactic acid resin and the modifier may be prepared by pre-mixing the polylactic acid resin, the modifier, and other components as needed. Examples of such mixing methods include mixing methods using a mixer such as a tumbler, ribbon blender, V blender, Henschel mixer, or Redige mixer.

[0059] As the extruder, any appropriate extruder can be used as long as the effects of the present invention are not impaired. In terms of being able to further exhibit the effects of the present invention, a twin-screw extruder is preferred.

[0060] The twin-screw extruder may be equipped with a strand die or a T-die. In this case, the extruded strand-shaped or sheet-shaped kneaded product may be cooled and cut into pellets using a pelletizer or the like.

[0061] The twin-screw extruder may be equipped with a pelletizing die (hot cut die), in which case the kneaded material is pelletized immediately after being extruded.

[0062] The temperature conditions for melt-kneading may vary depending on the size of the extruder, the discharge rate, etc., and any appropriate conditions may be adopted as long as the effects of the present invention are not impaired. For example, the temperature of the raw material feed section is preferably set to 100°C to 200°C.

[0063] The rotation speed of the extruder can vary depending on the size of the extruder, the discharge rate, etc., and any appropriate condition can be adopted as long as the effects of the present invention are not impaired. Such a rotation speed is preferably, for example, 20 rpm to 800 rpm.

[0064] The modified polylactic acid resin may be dried. Typically, the modified polylactic acid resin may be obtained by cooling a strand-shaped kneaded product extruded from a twin-screw extruder equipped with a strand die, cutting the resulting pellets with a pelletizer, or the like, and drying the pellets.

[0065] The modified polylactic acid resin can be produced using any appropriate apparatus as long as the effects of the present invention are not impaired. For example, the modified polylactic acid resin can be produced using a production apparatus such as that shown in FIG.

[0066] In Figure 1, for example, polylactic acid resin and modifier as raw materials fed into a hopper 11 are melt-kneaded by a twin-screw extruder 30, and the strand-shaped kneaded material extruded from a strand die 3 is cooled by a cooling device 6, then pelletized by a pelletizer 4, and dried by a drying device 5 to obtain a modified polylactic acid resin.

[0067] <1-1-b. Biodegradable Aliphatic-Aromatic Copolyester Resin (B)> As the biodegradable aliphatic-aromatic copolyester resin (B), any appropriate aliphatic-aromatic copolyester resin having biodegradability can be used as long as it does not impair the effects of the present invention. The biodegradable aliphatic-aromatic copolyester resin (B) may be one type or two or more types.

[0068] Examples of the biodegradable aliphatic-aromatic copolyester resin (B) include copolymers containing aliphatic dicarboxylic acid units, aromatic dicarboxylic acid units, and chain aliphatic and / or alicyclic diol units.

[0069] Examples of dicarboxylic acid components that provide aliphatic dicarboxylic acid units include succinic acid, adipic acid, suberic acid, sebacic acid, and dodecanedioic acid, with succinic acid and adipic acid being preferred.

[0070] Examples of aromatic dicarboxylic acid components that provide aromatic dicarboxylic acid units include terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid. Terephthalic acid and isophthalic acid are preferred, and terephthalic acid is more preferred.

[0071] Examples of the diol component that provides the chain aliphatic and / or alicyclic diol unit include ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. Preferred are ethylene glycol and 1,4-butanediol, and more preferred is 1,4-butanediol.

[0072] The biodegradable aliphatic-aromatic copolyester resin (B) may additionally be, for example, polybutylene adipate terephthalate (PBAT), which is a copolymer of 1,4-butanediol, adipic acid, and terephthalic acid.

[0073] <1-1-c. Foaming agents> The resin composition (C) typically contains a foaming agent, and the foaming agent may be one kind or two or more kinds.

[0074] Any appropriate foaming agent can be used as long as it does not impair the effects of the present invention. Examples of the foaming agent include volatile foaming agents that become gas at room temperature (23°C) and normal pressure (1 atmosphere) and decomposition type foaming agents that generate gas by thermal decomposition, and volatile foaming agents are preferred.

[0075] The volatile blowing agent is preferably an organic compound whose boiling point is equal to or lower than the softening point of the polylactic acid resin and which is gaseous or liquid at normal pressure. Specific examples include aliphatic hydrocarbons such as propane, n-butane, isobutane, pentane (n-pentane, isopentane, neopentane), and n-hexane; alicyclic hydrocarbons such as cyclopentane and cyclopentadiene; ketones such as acetone and methyl ethyl ketone; alcohols such as methanol, ethanol, and isopropyl alcohol; low-boiling ether compounds such as dimethyl ether, diethyl ether, dipropyl ether, and methyl ethyl ether; and halogen-containing hydrocarbons such as trichloromonofluoromethane and dichlorodifluoromethane. Inorganic gases such as carbon dioxide, nitrogen, and ammonia may also be used as the volatile blowing agent. Among these, the volatile blowing agent is preferably at least one selected from n-butane, isobutane, n-pentane, isopentane, neopentane, cyclopentane, and cyclopentadiene, and more preferably at least one selected from n-butane, isobutane, n-pentane, and isopentane, in terms of being able to further exhibit the effects of the present invention.

[0076] Examples of decomposition type foaming agents include azodicarbonamide, dinitrosopentamethylenetetramine, sodium bicarbonate, or a mixture of an organic acid such as citric acid or its salt with a bicarbonate.

[0077] The amount of the foaming agent used can be appropriately set depending on the purpose. The amount of the foaming agent used is preferably 0.1 to 10.0 parts by mass, more preferably 0.3 to 7.0 parts by mass, even more preferably 0.5 to 5.0 parts by mass, and particularly preferably 0.8 to 3.0 parts by mass, relative to 100 parts by mass of the total amount of the biodegradable aliphatic polyester resin (A) and the biodegradable aliphatic-aromatic copolyester resin (B).

[0078] <1-1-d. Foam adjuster> The resin composition (C) may contain a cell control agent, and the cell control agent may be one kind or two or more kinds.

[0079] Examples of foam regulators include higher fatty acid amides, partial esters of higher fatty acids and alcohols, talc, calcium carbonate, mica, citric acid, sodium bicarbonate, polytetrafluoroethylene, aluminum hydroxide, and silica. Examples of higher fatty acid amides include fatty acid monoamides such as oleic acid amide, stearic acid amide, and hydroxystearic acid amide; and fatty acid bisamides such as methylene bisstearic acid amide and ethylene bisstearic acid amide. Examples of higher fatty acids in the partial esters of higher fatty acids and alcohols include fatty acids having 15 or more carbon atoms, such as palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, and behenic acid. Examples of partial esters of higher fatty acids and alcohols include stearic acid monoglyceride and stearic acid diglyceride.

[0080] The content of the cell control agent in the resin composition (C) is preferably 0.01% by mass to 20% by mass, more preferably 0.1% by mass to 10% by mass, even more preferably 0.2% by mass to 5.0% by mass, and particularly preferably 0.3% by mass to 4.0% by mass, in order to further exhibit the effects of the present invention.

[0081] <1-1-e. Nucleating Agents> The resin composition (C) may contain a nucleating agent. The nucleating agent may be one type only, or two or more types may be used. The nucleating agent is preferably a substance that functions like a plasticizer and can promote the crystallization of polylactic acid.

[0082] As the crystal nucleating agent, for example, a reaction product (X) of (component a) at least one selected from the group consisting of polyols and polyol dehydration condensates, (component b) an alkylene oxide containing 50% by mass or more of ethylene oxide, and (component c) a fatty acid having 12 to 24 carbon atoms can be used.

[0083] Preferred examples of the polyol in (component a) include glycerin, erythritol, pentaerythritol, xylitol, sorbitol, mannitol, galactitol, and maltitol. Use of such polyols can further improve the impact resistance of the biodegradable polyester resin foam sheet according to the embodiment of the present invention.

[0084] Examples of the alkylene oxide in (component b) include ethylene oxide, propylene oxide, butylene oxide, and isobutylene oxide.

[0085] Examples of fatty acids having 12 to 24 carbon atoms in (component c) include saturated fatty acids such as dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), pentadecanoic acid (pentadecylic acid), hexadecanoic acid (palmitic acid), heptadecanoic acid (margaric acid), octadecanoic acid (stearic acid), icosanoic acid (arachidic acid), henicosanoic acid (henicosylic acid), docosanoic acid (behenic acid), and tetracosanoic acid (lignoceric acid); monounsaturated fatty acids such as myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, eicosenoic acid, and erucic acid; diunsaturated fatty acids such as linoleic acid and triunsaturated fatty acids such as linolenic acid; and mixtures of multiple fatty acids such as coconut oil fatty acids. Among these, dodecanoic acid (lauric acid) and octadecanoic acid (stearic acid) are preferred.

[0086] The reaction product (X) preferably has an oxyethylene group content of 20% by mass to 95% by mass, more preferably 30% by mass to 95% by mass, in order to further improve the impact resistance of the biodegradable polyester resin foam sheet according to an embodiment of the present invention.

[0087] The reaction product (X) may be either a saturated ester in which all of the hydroxyl groups of the polyol and the polyol dehydration condensate are esterified with fatty acids, or a partial ester in which some of the hydroxyl groups are esterified, in order to further improve the impact resistance of the biodegradable polyester resin foam sheet according to an embodiment of the present invention.

[0088] The reaction product (X) preferably has an average of more than 2 and not more than 9 ester groups, more preferably more than 2.5 and not more than 6 ester groups, in the molecule, in order to further improve the impact resistance of the biodegradable polyester resin foam sheet according to an embodiment of the present invention.

[0089] Examples of methods for producing the reaction product (X) include a method in which a polyol and a fatty acid are reacted under heating to esterify the polyol, and then ethylene oxide is added in an autoclave under heating; a method in which a dehydration condensate of a polyol is reacted with a fatty acid to esterify the polyol, and then ethylene oxide is added in the same manner as the above method; a method in which ethylene oxide is added to at least one selected from the group consisting of polyols and polyol dehydration condensates, and then a fatty acid is reacted; and a method in which a fatty acid ester is first synthesized from a fatty acid and a monohydric alcohol having a short carbon number (e.g., methanol, ethanol), and then esterification is carried out with at least one selected from the group consisting of polyols and polyol dehydration condensates, and then ethylene oxide is added in the same manner as the above method.

[0090] As the crystal nucleating agent, for example, a fatty acid amide can be used. Examples of the fatty acid amide include at least one fatty acid amide selected from the group consisting of fatty monoamides, fatty acid bisamides, hydroxyl group-containing fatty acid monoamides, and hydroxyl group-containing fatty acid bisamides, which are derived from fatty acids having 8 to 24 carbon atoms. Examples of such fatty acid amides include fatty acid bisamides such as N,N'-ethylenebisstearamide; and hydroxyl group-containing fatty acid bisamides such as N,N'-ethylenebis(12-hydroxystearamide) and N,N'-xylylenebis(12-hydroxystearamide).

[0091] Examples of nucleating agents that can be used include hydrocarbons such as liquid paraffin, paraffin wax, and synthetic polyethylene wax; metal soaps such as zinc stearate, calcium stearate, and magnesium stearate; polyethylene glycols such as ethylene glycol, diethylene glycol, and higher polyethylene glycols; propylene glycol, dipropylene glycol, and higher polypropylene glycols; 1,3-butylene glycol, 1,4-butylene glycol, and their polymers, polybutylene glycols; and polyhydric alcohols such as glycerin, diglycerin, and higher polyglycerins.

[0092] The above-described crystal nucleating agents, which function like plasticizers, can migrate to the surface layer of the biodegradable polyester resin foam sheet according to an embodiment of the present invention and exude from the surface, a phenomenon known as "bleed-out." These agents tend to bleed out of the biodegradable polyester resin foam sheet during thermoforming. While this is typically considered problematic, it can be advantageous in providing adequate slippage with the molding die and improving the thickness uniformity of the molded body. In other words, if adequate slippage is not achieved between the molding die and the biodegradable polyester resin foam sheet, the biodegradable polyester resin foam sheet may be locally stretched, resulting in thin-walled areas in the molded body. However, the use of such crystal nucleating agents can mitigate this problem. Furthermore, the tendency to bleed out reduces the amount of agent remaining in the molded body, thereby preventing further crystallization-induced distortion in the event of unintended heating of the molded body.

[0093] The amount of the nucleating agent is preferably 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, even more preferably 2 to 12 parts by mass, and particularly preferably 3 to 12 parts by mass, relative to 100 parts by mass of the total of the biodegradable aliphatic polyester resin (A) and the biodegradable aliphatic-aromatic copolyester resin (B).

[0094] <1-1-f. Other ingredients> The resin composition (C) may contain any appropriate other component within the scope of the present invention. Such other components may be one type only or two or more types. Examples of such other components include foaming aids, other resins, pigments, radiant heat transfer suppressing components, crosslinkers, plasticizers, stabilizers, fillers, lubricants, colorants, antioxidants, antistatic agents, spreading agents, weather resistance agents, flame retardants, UV absorbers, light stabilizers, antioxidants, antifogging agents, fragrances, and antibacterial agents.

[0095] The content of other components in the resin composition (C) may be any appropriate content ratio within the range that does not impair the effects of the present invention, and such a content ratio is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 1% by mass or less.

[0096] ≪1-2. Manufacturing of biodegradable polyester resin foam sheets≫ The biodegradable polyester resin foam sheet according to the embodiment of the present invention is obtained by melt-kneading the resin composition (C) in an extruder and extrusion-foaming it.

[0097] Any components contained in the resin composition (C) may be pre-mixed as necessary before being fed into the extruder. Examples of such a mixing method include a mixing method using a mixer such as a tumbler, ribbon blender, V blender, Henschel mixer, or Redige mixer.

[0098] Any appropriate extruder may be used as the extruder as long as it does not impair the effects of the present invention. In terms of being able to more effectively exhibit the effects of the present invention, a tandem extruder is preferably used as the extruder.

[0099] The tip of the tandem extruder may be equipped with any appropriate die within the scope of not impairing the effects of the present invention so as to finally obtain a biodegradable polyester resin foam sheet, and preferably may further be equipped with a cooling mandrel, a take-up roller for taking up the biodegradable polyester resin foam sheet as a raw roll, and the like.

[0100] The biodegradable polyester resin foam sheet can be produced using any appropriate apparatus as long as the effects of the present invention are not impaired. For example, the biodegradable polyester resin foam sheet can be produced using a production apparatus such as that shown in FIG.

[0101] The production apparatus shown in Figure 2 includes a tandem extruder 10 and a circular die CD that discharges the resin composition (C) melt-kneaded in the tandem extruder 10 into a cylindrical shape. The production apparatus also includes a cooling device CL that air-cools the foamed sheet discharged into a cylindrical shape from the circular die CD, a mandrel MD that expands the cylindrical foamed sheet into a cylindrical shape of a predetermined size, a slitting device that slits the foamed sheet after passing through the mandrel MD to divide it into two sheets, and a take-up roller 22 that winds up the slit foamed sheet 1 after passing it through multiple rollers 21. An extruder upstream of the tandem extruder 10 (hereinafter also referred to as "first extruder 10a") is provided with a hopper 11 for introducing a biodegradable polyester resin, which is a raw material for the foamed sheet, and a gas inlet 12 for supplying a blowing agent into the cylinder. An extruder (hereinafter also referred to as "second extruder 10b") for melt-kneading a resin composition (C) containing a biodegradable polyester resin and a foaming agent is provided downstream of the first extruder 10a.

[0102] The temperature conditions for melt-kneading may vary depending on the size and discharge rate of the extruder, and any appropriate conditions may be adopted as long as the effects of the present invention are not impaired. For example, the temperature of the raw material feed section of the upstream extruder 10a is preferably set to 100°C to 200°C, more preferably 140°C to 200°C, the temperature after the upstream extruder 10a is preferably set to 120°C to 300°C, more preferably 140°C to 270°C, and the temperature of the downstream extruder 10b is preferably set to 100°C to 250°C, more preferably 120°C to 220°C.

[0103] The rotation speed of the extruder may vary depending on the size of the extruder, the discharge rate, etc., and any appropriate condition may be adopted as long as the effects of the present invention are not impaired. For example, the rotation speed of the upstream extruder 10a is preferably 10 rpm to 300 rpm, and that of the downstream extruder 10b is preferably 5 rpm to 200 rpm.

[0104] 2. Biodegradable polyester resin foam molding The biodegradable polyester resin foam molded article according to the embodiment of the present invention is obtained by molding the biodegradable polyester resin foam sheet according to the embodiment of the present invention.

[0105] The biodegradable polyester resin foam molded article according to an embodiment of the present invention can be obtained by, for example, heat-softening the biodegradable polyester resin foam sheet according to an embodiment of the present invention, and then thermoforming the sheet using a mold by a vacuum molding method and / or a pressure molding method, or a matched mold molding method or a plug-assist molding method that is an application of the vacuum molding method and / or a pressure molding method.

[0106] The biodegradable polyester resin foam molded article according to the embodiment of the present invention can be used as, for example, food containers such as trays, cups, bowls, lunch boxes, fruit containers, vegetable containers, etc.; cushioning materials such as cushioning materials for electrical appliances and cushioning materials for precision instruments; etc. [Example]

[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring and evaluating each property are as follows.

[0108] <Maximum point energy> The maximum point energy of the biodegradable polyester resin foam sheet was measured in accordance with ASTM D-3763-15. Specifically, measurements were taken using a CEAST "CEAST9350" drop weight impact tester and measurement software "CEAST VIEW" with a test specimen size of 100 mm length x 100 mm width (thickness is the thickness of the biodegradable polyester resin foam sheet), a test speed of 1.76 m / sec, a drop weight load of 1.9265 kg, a test specimen support span of φ76 mm, and a 4.5 kN instrumented tap (hemispherical tip φ12.7 mm). The number of test specimens was a minimum of five, and the test specimens were conditioned for 40 hours in an environment according to Procedure A of ASTM D618-13 (23±2°C, relative humidity 50±10%), after which measurements were carried out in the same temperature environment. The maximum point energy was calculated automatically by the measurement software from the integral value of the graph obtained by the measurement.

[0109] <Flexibility> The flexibility of the biodegradable polyester resin foam sheet was measured in accordance with JIS K7171:2016. Measurements were carried out using Shimadzu Corporation's "Autograph AG-X plus 100kN" universal testing machine and Shimadzu Corporation's "TRAPEZIUM X" universal testing machine data processing. Test specimens were cut from biodegradable polyester resin foam sheets in the extrusion direction (MD) to a width of 25 mm, length of 40 mm, and original thickness. Three test specimens were used. The test specimens were conditioned for 16 hours in a standard atmosphere of JIS K 7100:1999, symbol "23 / 50," Class 2, before being used for measurement. Measurements were performed under the same conditions, with a test speed of 1 mm / min. A pressure wedge with a radius of 5R and a support point with a tip radius of 2R was used, with a support distance of 32 mm. The test specimen was placed on the support point with the air-cooled surface facing upward. From the obtained graph, the load region where the slope is maximum was set, and the slope of each test piece was determined by data processing of the universal testing machine, and this slope was taken as the flexibility.

[0110] <Surface hardness> The biodegradable polyester resin foam sheet was cut into a strip of 50 mm wide and 550 mm long to prepare a test piece. A rubber hardness tester (spring-type hardness tester) (manufactured by Kobunshi Keiki Co., Ltd., product name "CS type") was pressed against the surface of the obtained test piece, and measurements were taken at 100 mm intervals along the length (5 locations), and the arithmetic average of the measurements was taken as the surface hardness.

[0111] <Open cell ratio> Several sheet samples measuring 25 mm in length and 25 mm in width were cut out from the biodegradable polyester resin foam sheet, and the cut samples were stacked together without leaving any gaps to form a measurement sample with a thickness of 25 mm. The outer dimensions of this measurement sample were measured to 1 / 100 mm using a Mitutoyo Digimatic Caliper, and the apparent volume (cm 3 ) was sought. Next, using an air comparison hydrometer, Model 1000 (Tokyo Science Co., Ltd.), the volume (cm) of the sample to be measured was measured by the 1-1 / 2-1 atmospheric pressure method. 3 ) was sought. The open cell rate (%) was calculated using these determined values ​​and the following formula, and the average value for five test pieces was calculated. The measurement was carried out in a JIS K7100-1999, symbol 23 / 50, grade 2 environment after conditioning the measurement sample for 16 hours in the JIS K7100-1999, symbol 23 / 50, grade 2 environment. In addition, the air comparison hydrometer was calibrated using standard bulbs (large 28.9cc, small 8.5cc). Open cell rate (%) = [(apparent volume - volume measured with air comparison hydrometer) / apparent volume] x 100 (%)

[0112] <Expansion ratio> The expansion ratio of the biodegradable polyester resin foam sheet was determined by determining the apparent density (ρ1) of the biodegradable polyester resin foam sheet, determining the density (true density: ρ0) of the resin composition constituting the biodegradable polyester resin foam sheet, and dividing the true density (ρ0) by the apparent density (ρ1). Expansion ratio = true density (ρ0) / apparent density (ρ1) The density of the biodegradable polyester resin foam sheet can be determined by the method described in JIS-K7222:1999 "Foamed plastics and rubber - Measurement of apparent density", and specifically, it was determined by the following method. (Density measurement method) Biodegradable polyester resin foam sheet, 100cm 3 The above samples were cut without changing the original cell structure, and the samples were conditioned for 16 hours in a JIS K7100:1999 symbol 23 / 50, class 2 environment, after which the dimensions and mass were measured and the density was calculated using the following formula. Apparent density (g / cm 3 ) = mass of sample (g) / volume of sample (cm 3 ) The dimensions of the samples were measured using a "DIGIMATIC" CD-15 type manufactured by Mitutoyo Corporation. The density of the resin composition constituting the biodegradable polyester resin foam sheet was determined by measuring a sample of the biodegradable polyester resin foam sheet that had been made non-foamed by, for example, heat pressing, based on the Archimedes method (a liquid weighing method in JIS-K8807:2012 "Methods for determining density and specific gravity of solids").

[0113] <Melt tension measurement> The melt tension was measured using a Capillograph 1D (manufactured by Toyo Seiki Seisakusho, Ltd.) and a Rheotens 71.97 (manufactured by Gottfert). The sample was pre-dried under vacuum at 90°C for 5 hours. The Rheotens 71.97 was installed so that the distance from the capillary die outlet to the measurement section was 80 mm. First, the sample was filled into a 9.55 mm diameter barrel heated to a test temperature of 190°C and preheated for 5 minutes. The measurement time, including the preheating time from filling the barrel, should not exceed 10 minutes. Next, a piston was inserted from the top of the barrel, and the molten resin was extruded into a string-like shape through a capillary die (diameter 2.095 mm, length 8 mm, inlet angle 90° (conical)). The piston descending speed (20 mm / min) was maintained constant, and the extruded string-like material was passed through a Rheotens wheel (wheel spacing: top 0.6 mm–0.8 mm, bottom 1.0 mm), with an initial velocity of 6.92 mm / s and an acceleration of 10 mm / s. 2 The melt tension of the sample was measured while gradually increasing the temperature. Regarding the measurement results, the average of the maximum and minimum tension values ​​immediately before the point at which the string-like material broke was taken as the melt tension of the sample. When there was only one maximum point on the tension chart, the maximum value was taken as the melt tension. When the string-like material became thinner and the winding became idle, this point was regarded as the breaking point, and the average of the maximum and minimum tension values ​​immediately before that point was taken as the melt tension of the sample. [Measurement conditions for "Capilograph 1D"] Die: diameter 2.095 mm, length 8 mm, inlet angle 90 degrees (conical) Barrel diameter: 9.55mm Piston speed: 20mm / min Measurement temperature: 190℃ [Measurement conditions for "Rheotens 71.97"] Wheel spacing: Top 0.6mm~0.8mm, bottom 1.0mm Acceleration: 10mm / s 2 Pulling speed: Initial speed 6.92 mm / s

[0114] <MFR(メルトマスフローレイト)> MFR was measured in accordance with JIS K 7210:1999. Specifically, it was measured by "b) Measuring the time it takes for a piston to move a specified distance" as described in Method B of the same standard. MFR was measured using a Melt Flow Index Tester (Automatic) 120-SAS (Yasuda Seiki Seisakusho Co., Ltd.). The samples were vacuum dried at 90°C for 5 hours, then sealed and stored in a desiccator until immediately before measurement. Measurements were performed three times, and the average was used as the MFR (g / 10 min). The measurement conditions were as follows: Sample: 3g to 8g Preheat (1): 200 seconds Preheat (2): 30 seconds Test temperature: 190℃ Test load: 21.18N Piston travel distance (interval): 25mm

[0115] <Evaluation of processability> The processability of the biodegradable polyester resin foam sheet was evaluated based on the occurrence of chipping and cutting chips during groove processing. A V-groove spanning the entire width of a biodegradable polyester resin foam sheet in the width direction perpendicular to the extrusion direction was formed by cutting, and the sheet was then cut into 35 mm wide strips that were long in the extrusion direction perpendicular to the V-groove direction.The generation of chips and chips was evaluated. At this time, if "chipping" or "chips" occurred in the cut area, it was judged as a poor "x", and if no "chipping" or "chips" occurred, it was judged as a good "o".

[0116] [Production Example 1]: Production of modified polylactic acid resin Polylactic acid resin (Nature Works Biopolymer Ingeo 6202D, MFR = 11.2 g / 10 min, density = 1.24 g / cm 3 100 parts by mass of tert-butylperoxyisopropyl monocarbonate (manufactured by Kayaku Nouryon Co., Ltd., "Trigonox BPIC-75", 1-minute half-life temperature T1: 158.8°C) were mixed and stirred in a ribbon blender to obtain a mixture. The resulting mixture was fed into a twin-screw extruder (L / D=31.5) with a diameter of 57 mm. The temperature of the feed section was set to 170°C, and the temperatures thereafter to 200°C. The mixture was melt-kneaded in the twin-screw extruder at a rotation speed of 100 rpm, and the kneaded mixture was extruded in the form of strands at a discharge rate of 50 kg / h from a die with a diameter of 3 mm and 18 holes attached to the tip of the twin-screw extruder. Next, the extruded strand-like kneaded product was passed through a 2 m long cooling water tank containing water at 30°C to cool it. The cooled strand was cut with a pelletizer to obtain pellets of the modified polylactic acid resin. The resulting modified polylactic acid resin had a melt tension of 50 cN and an MFR of 1.5 g / 10 min.

[0117] [Example 1] Resin component (modified polylactic acid resin obtained in Production Example 1: 97% by mass) and polybutylene adipate terephthalate (BASF, "ecoflex C1200", density = 1.25 g / cm 3 100 parts by mass of a cellulose acylate (3.0% by mass) and 1.0 part by mass of a cell regulator (manufactured by Matsumura Sangyo Co., Ltd., "Crown Talc") were dry blended to prepare a mixture. In a tandem extruder equipped with a first extruder (upstream) with a diameter of φ50 mm and a second extruder (downstream) with a diameter of φ65 mm, the obtained mixture was fed through a hopper to the first extruder with a diameter of φ50 mm and heated to melt at 220°C. Thereafter, 1.2 parts by mass of butane (isobutane / normal butane=70 / 30) was pressure-fed into the first extruder as a foaming agent, and melt-mixed with the above mixture. The molten mixture was then transferred to a second extruder with a diameter of 65 mm, cooled to about 170°C, and then extruded and foamed through a circular die with a diameter of 70 mm at a discharge rate of 30 kg / h to obtain a cylindrical foam. The obtained cylindrical foam was placed on a φ206 mm mandrel whose inside was cooled with water at about 20°C, and its outer surface was cooled and molded by blowing air onto it using an air ring larger than the diameter of the mandrel.Then, it was cut at one point on the circumference using a cutter to obtain a strip-shaped polylactic acid resin foam sheet (1). The results are shown in Table 1.

[0118] [Example 2] The same procedure as in Example 1 was carried out, except that the amount of modified polylactic acid resin as the resin component was changed to 95% by mass and the amount of polybutylene adipate terephthalate was changed to 5% by mass, to obtain a strip-shaped polylactic acid resin foam sheet (2). The results are shown in Table 1.

[0119] [Example 3] The same procedure as in Example 1 was carried out, except that the amount of modified polylactic acid resin as the resin component was changed to 90% by mass and the amount of polybutylene adipate terephthalate was changed to 10% by mass, to obtain a strip-shaped polylactic acid resin foam sheet (3). The results are shown in Table 1.

[0120] [Example 4] The same procedure as in Example 1 was carried out, except that the amount of modified polylactic acid resin in the resin component was changed to 85% by mass and the amount of polybutylene adipate terephthalate was changed to 15% by mass, to obtain a strip-shaped polylactic acid resin foam sheet (4). The results are shown in Table 1.

[0121] [Example 5] As the resin component, the amount of modified polylactic acid resin was changed to 80 mass%, the amount of polybutylene adipate terephthalate was changed to 10 mass%, and a crystal nucleating agent (TRIBIO S920MB (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), density = 1.20 g / cm) was further added. 3 The same procedure as in Example 1 was carried out except that 10% by mass of the polylactic acid resin foam sheet (5) was added, to obtain a strip-shaped polylactic acid resin foam sheet (5). The results are shown in Table 1.

[0122] [Comparative Example 1] A strip-shaped polylactic acid resin foam sheet (C1) was obtained in the same manner as in Example 1, except that the amount of modified polylactic acid resin as the resin component was 100% by mass and polybutylene adipate terephthalate was not used. The results are shown in Table 1.

[0123] Comparative Example 2 A strip-shaped polylactic acid resin foam sheet (C2) was obtained in the same manner as in Example 1, except that the amount of modified polylactic acid resin as the resin component was changed to 70% by mass and the amount of polybutylene adipate terephthalate was changed to 30% by mass. The results are shown in Table 1.

[0124] [Table 1] [Industrial Applicability]

[0125] The biodegradable polyester resin foam sheet of the present invention can be easily molded into a variety of shapes and can therefore be used as a raw material for various molded products, including packaging materials. [Explanation of symbols]

[0126] 1 foam sheet 3 strand die 4 Pelletizer 5 Drying equipment 6 Cooling device 10 Tandem Extruder 10a First extruder 10b Second extruder 11 Hopper 12 Gas inlet 21 Laura 22 Winding roller 30 Twin-screw extruder

Claims

1. A biodegradable polyester resin foam sheet obtained by foaming a resin composition (C) containing a biodegradable aliphatic polyester resin (A) and a biodegradable aliphatic-aromatic copolyester resin (B), the mass ratio of the biodegradable aliphatic polyester resin (A) to the biodegradable aliphatic-aromatic copolyester resin (B) is (A):(B)=75:25 to 97:3; Biodegradable polyester resin foam sheet.

2. The biodegradable polyester resin foam sheet according to claim 1, having a maximum point energy of 0.30 J or more as measured in accordance with ASTM D-3763-15.

3. The biodegradable polyester resin foam sheet according to claim 1, having a flexibility measured in accordance with JIS K7171:2016 of 2.0 N / mm to 9.0 N / mm.

4. 2. The biodegradable polyester resin foam sheet according to claim 1, having a surface hardness of 94 or less.

5. The biodegradable polyester resin foam sheet according to claim 1, having a thickness of 0.5 mm to 7 mm.

6. 2. The biodegradable polyester resin foam sheet according to claim 1, having an open cell ratio of 50% or less.

7. The biodegradable polyester resin foam sheet according to claim 1, having an expansion ratio of 4 to 20 times.

8. The biodegradable polyester resin foam sheet according to claim 1, wherein the biodegradable aliphatic polyester resin (A) has a melt tension of 20 cN or more at 190°C.

9. The biodegradable polyester resin foam sheet according to claim 1, wherein the biodegradable aliphatic polyester resin (A) has an MFR of 5.0 g / 10 min or less.

10. The biodegradable polyester resin foam sheet according to claim 1 , wherein the biodegradable aliphatic polyester resin (A) is a polylactic acid resin (P).

11. The biodegradable polyester resin foam sheet according to claim 10, wherein the polylactic acid resin (P) is a modified polylactic acid resin.

12. 2. The biodegradable polyester resin foam sheet according to claim 1, wherein the biodegradable aliphatic-aromatic copolyester resin (B) is polybutylene adipate terephthalate.

13. A biodegradable polyester resin foam molded article obtained by molding the biodegradable polyester foam sheet according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Polylactic acid based molded article and its manufacturing method

    JP2004269588A

  • Polylactic acid-based resin foam sheet, and sheet molding

    JP2022057271A